Race, Reform, & Progressive Prosecution - Fryer, Daniel (2020)
The progressive prosecution movement is one of the most recent efforts to reform the United States criminal justice system. In this Article, I analyze two assumptions that appear to be guiding this movement. The first is that prosecutors have unilateral power to change the system. The second is that those who bear the biggest burden of our current system—black Americans—would be the primary beneficiaries of the decarceration proposals advanced by progressive prosecutors. I argue that each of these assumptions is misguided. A successful criminal justice reform movement must recognize the contingent power of prosecutors and actively seek to advance racial justice on top of its decarceration efforts. To avoid exacerbating the problems they intend to correct, reformists must reexamine the principles underlying the movement and the aims they expect to achieve